Effects of Nutritional Counselling on Dietary Intake and Nutritional Status of Pregnant Women Attending Health Facilities In Dang Province 5 Nepal - Pradhan, Jaya Laxmi; Devkota, Pooja; Sen, Sita Kumari; Bhatta, Nirmala (Journal of Nepal Health Research Council, 2025)
Background: Proper nutrition counselling on healthy food habit to all pregnant women can be a strong weapon to achieve good health of mothers as well as healthy offspring. The main objective of this research was to assess the effectiveness of nutritional counseling on dietary intake and nutritional status of pregnant women. Methods: Quasi-experimental research design was used to evaluate the effectiveness of nutritional counselling on dietary intake and nutritional status of pregnant women. The study area was chosen based on nonprobability purposive sampling technique and 110 participants who were pregnant before 20 weeks of gestation were included in the study who attended district hospital Lamahi and health post of Sisahaniya, Dang. Risults: Mid Upper Arm Circumference (MUAC) measurement of pregnant women showed that 11.8% pregnant women were malnourished (MUAC <22cm) before intervention. The proportion of MUAC measurement improved after nutritional counseling (4.5%). Almost all participants consumed rice, and roti as main foods. Frequency of consuming dal, green vegetables, fruits, milk and milk products, meat, fish, and egg increased after nutrition counseling. The result indicated that the consumption of carbohydrate, protein, fat and energy increased after nutrition counseling (Carbohydrate-226 vs 289g, protein- 65 vs 77g, fat- 43 vs 50g, energy- 1648 vs 2041kcal). Conclusions: Maternal nutrition during pregnancy is crucial for achieving healthy maternal and fetal outcomes. Nutrition counselling showed positive effects on nutritional status of pregnant women. Thus, nutrition counselling is essential for all pregnant women. It should be a major part of Antenatal care service to all pregnant women in Nepal. Keywords: Malnutrition; malnutrition; maternal and fetal outcome; nutrition counseling; underweight.